Infectious Diseases and Vaccine Sciences: Strategic Directions - Luby, Stephen P; Brooks, W Abdullah; Zaman, K; Hossain, Shahed; Ahmed, Tahmeed (Journal of Health, Population and Nutrition, 2009)
Despite substantial progress, infectious diseases remain important causes of ill-health and premature deaths in Bangladesh. Bangladesh has experienced a >90% reduction in the incidence of deaths due to childhood diarrhoea over the last 25 years. Further reductions can be achieved through the introduction of effective vaccines against rotavirus and improvements in home hygiene, quality of drinking-water, and clinical case management, including appropriate use of oral rehydration solution and zinc. Pneumonia is now the leading cause of childhood deaths in Bangladesh, and the pneumonia-specific child mortality is largely unchanged over the last 25 years. Reductions in mortality due to pneumonia can be achieved through the introduction of protein conjugate vaccines against Haemophilus influenza type b and Streptococcus pneuÂmoniae, improvements in case management, including efforts to prevent delays in providing appropriate treatment, and the wider use of zinc. Tuberculosis is responsible for an estimated 70,000 deaths each year in Bangladesh. Although services for directly-observed therapy have expanded markedly, improved case finding and involvement of private practitioners will be important to reduce the burden of disease. Key words: Communicable diseases; Diarrhoea; Mortality; Pneumoniea; Tuberculosis; Vaccine Sciences; Bangladesh doi:10.3329/jhpn.v26i3.1897 J Health Popul Nutr 2008 Sept:26(3):295-310